Microplastic ingestion by pelagic and demersal fish species from the Eastern Central Atlantic Ocean, off the Coast of Ghana. (April 2020) - Adika, Stella Aseye; Mahu, Edem; Crane, Richard; Marchant, Rob; Montford, Judith; Folorunsho, Regina; Gordon, Christopher
Abstract: We present data on the occurrence of microplastics in fish from the Guinea current region off Ghana's Coast. Frequency of occurrence of microplastics in the fish species followed the order: Sardinella maderensis (41%) > Dentex angolensis > (33%) > Sardinella aurita (26%). Mean numbers of microplastics ingested were 40.0 ± 3.8, 32.0 ± 2.7 and 25.7 ± 1.6 for S . maderensis, D . angolensis and S . aurita respectively. Industrially produced pellets were the most dominant (31%) microplastic type followed by microbeads (29%), burnt film plastics (22%) and unidentified fragments (9%). Microfibers (2%), threads (2%) and foams (<0.1%) were the least occurring microplastics in the fish species. Condition factors estimated for D . angolensis and S . aurita were >1 and below 1 for S . maderensis . The findings of the study show the common occurrence of microplastics in fish stocks and pave the way for future studies on microplastics in this Region. Highlights: The study presents baseline data on microplastic occurrence in three fish species from the Gulf of Guinea Microplastics were found in the gastrointestinal tract of all three fish species Microbeads and industrially produced pellets dominated the guts of the all three fish species More research work is needed to verify the source of microplastics in the Region.